Peer victimization (bullying) on mental health, behavioral problems, cognition, and academic performance in preadolescent children in the ABCD Study - Menken, Miriam S.; Isaiah, Amal; Liang, Huajun; Rivera, Pedro Rodriguez; Cloak, Christine C.; Reeves, Gloria; Lever, Nancy A.; Chang, Linda (Frontiers in Psychology, 2022)
Objective: Peer victimization is a substantial early life stressor linked to psychiatric symptoms and poor academic performance. However, the sex-specific cognitive or behavioral outcomes of bullying have not been well-described in preadolescent children. Methods: Using the baseline dataset of the Adolescent Brain Cognitive Development (ABCD) Study 2.0.1 data repository (N=11,875), we evaluated associations between parent-reported bullying victimization, suicidality (suicidal ideation, intent, and/or behavior), and non-suicidal self-injury (NSSI), as well as internalizing and externalizing behavioral problems, cognition, and academic performance. Results: Of the 11,016 9-10-year-old children included in the analyses (5,263 girls), 15.3% experienced bullying victimization, as reported by the primary caregiver. Of these, boys were more likely to be bullied than girls (odds ratio [OR], 1.2 [95% CI, 1.1-1.3]; P=0.004). Children who were bullied were more likely to display NSSI or passive suicidality (OR, 2.4 [95% CI, 2.0-2.9]; P<0.001) and active suicidality (OR, 3.4 [95% CI, 2.7-4.2]; P<0.001). Bullied children also had lower cognitive scores, greater behavioral problems, and poorer grades (P<0.001). Across all participants, boys had poorer grades and greater behavioral problems than girls; however, bullied boys had greater behavioral problems than girls in several areas (P<0.001). Compared to their non-bullied peers, bullied children with greater non-suicidal self-injury or suicidality also had greater behavioral problems and poorer grades (P<0.001). Conclusions: These findings highlight the sex-specific effects of bullying, and the negative associations of bullying victimization with cognitive performance, behavioral problems, and academic performance. Future longitudinal studies will identify the natural history and neural correlates of these deficits during adolescence.